2022
DOI: 10.4103/jpbs.jpbs_9_22
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human PapillomaVirus and its Association with Potentially Malignant Disorders and Oral Squamous Cell Carcinoma

Abstract: Aim: This study was carried out with the objective of recognizing the involvement of human papillomavirus (HPV) in conditions of oral squamous cell carcinoma (OSCC) and oral potentially malignant conditions and lesions. Materials and Methods: OSCC samples from thirty patients were collected and thirty paraffin-embedded, oral premalignant specimens were collected. It was decided to use as a negative control samples gingiva from healthy individuals who had no prior histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Previous research has demonstrated the efficacy of corticosteroid treatments, whether applied topically or via injection, in reducing the size of OLP lesions [29][30][31][32][33]. The assessments provide a quantitative measure of lesion size in terms of standardized qualitative measures [34][35][36]. Several studies have specifically investigated and compared the effects of PRP and TA applications on OLP lesions, focusing on changes in lesion sizes [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the efficacy of corticosteroid treatments, whether applied topically or via injection, in reducing the size of OLP lesions [29][30][31][32][33]. The assessments provide a quantitative measure of lesion size in terms of standardized qualitative measures [34][35][36]. Several studies have specifically investigated and compared the effects of PRP and TA applications on OLP lesions, focusing on changes in lesion sizes [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Saliva offers several advantages, including easy and non-invasive sample collection, making it an attractive medium for biomarker analysis. [ 8 9 ]…”
Section: Discussionmentioning
confidence: 99%